(untitled) (Journal of economic and management development research, 2026)
In recent years, logistics and distribution have faced many challenges while promoting the development of e-commerce and economic growth. This article takes JD Logistics as an example to analyze the problems of excessive market competitiveness, poor delivery time, high logistics costs, and loss of professional talents in its distribution system based on the SCOR model, and proposes targeted optimization measures.